2009
DOI: 10.1007/s00540-009-0738-3
|View full text |Cite
|
Sign up to set email alerts
|

A randomized study of the effects of perioperative i.v. lidocaine on hemodynamic and hormonal responses for cesarean section

Abstract: Perioperative lidocaine is safe and effective in attenuating the maternal stress response to surgery for cesarean delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 27 publications
0
27
0
1
Order By: Relevance
“…24 Seven studies originated in the USA, [25][26][27][28][29][30][31] one in Belgium, 32 two in Taiwan, 14,33 three in Germany, 23,34,35 one in New Zealand, 36 three in Sweden, [37][38][39] two in China, 40,41 one in France, 42 three in Canada, [43][44][45] one in Mexico, 24 two in Saudi Arabia, 46,47 one in Israel, 48 one in the Republic of Korea 49 and one in Finland. 50 Studies were conducted in patients undergoing abdominal, cardiac, thoracic, orthopedic, or urologic surgery ( Table 1).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…24 Seven studies originated in the USA, [25][26][27][28][29][30][31] one in Belgium, 32 two in Taiwan, 14,33 three in Germany, 23,34,35 one in New Zealand, 36 three in Sweden, [37][38][39] two in China, 40,41 one in France, 42 three in Canada, [43][44][45] one in Mexico, 24 two in Saudi Arabia, 46,47 one in Israel, 48 one in the Republic of Korea 49 and one in Finland. 50 Studies were conducted in patients undergoing abdominal, cardiac, thoracic, orthopedic, or urologic surgery ( Table 1).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…50 Studies were conducted in patients undergoing abdominal, cardiac, thoracic, orthopedic, or urologic surgery ( Table 1). Source of sponsorship was not mentioned in 11 studies, [23][24][25][26][27]29,42,[45][46][47][48] while other studies received grants from foundations, national councils, or universities. No study reported industry sponsorship.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations